Peranan Profesi Kedokteran dan Sarana Pendukungnya dalam Upaya Perdamaian dan Pencegahan Perang Nuklirl) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1986)
ABSTRACT: Soedibjo Sardadi . The Role of the medical profession and its support system in the promotion of peace and the prevention of nuclear war In this article the author describes the present development of the war machine, and its actual and potential impact on medicine. The effects of nuclear explosion are briefly discussed and the possible roles of the medical profession is brought forth in facing the current global political situation. The ethical and moral foundation of medicine is emphasized in carrying out the professional social responsibility to preserve the comprehensive health of mankind.